MOBILE SENSORIMOTOR INTEGRATION ASSESSMENT IN SOCCER PLAYERS - Rollins, Kyrstin (My University, 2025)
Background: The purpose of this study is to establish metrics that work in the field to promptly identify and evaluate the level of sensorimotor integration impairment incurred by repetitive sub-concussive loading (RSCL). Repeated head impacts, even without clinical symptoms of mTBI, can cause neurocognitive and neurophysiological impairments. In contact sports, repetitive sub-concussive impacts may lead to mTBI-like deficits, increasing the risk of neurological injury, cognitive decline, and CTE. One study found CTE in 41.4% of contact sport athletes under 30 at death. With many neurological injuries going undetected, developing a rapid, in-field assessment is crucial to prevent further damage. We hypothesize that the use of wireless sensorimotor integration measurements can be harnessed to objectively evaluate sensorimotor integration following periods of exposure to RSCL in the field. Methods: Our approach is to integrate wireless measures of postural control, oculomotor control, and cortical activation with virtual reality (VR) to provide a comprehensive assessment of sensorimotor integration function, independent of a lab setting, following a single period of exposure to RSCL. Twenty participants will be chosen who are ages 18-50 who currently play, or have played within the past two years, organized soccer with no diagnosed concussions within the past year and no lower extremity injuries within the past three months. These participants will be outfitted with a Pedar in-hoe pressure distribution and gTEC EEG systems after consent is obtained. They will then participate in the pretest using the wireless measures listed above. Next, the participants will take part in the RSCL exposure period. For the RSCL exposure period, soccer players will engage in a heading training protocol. Following completion of the heading protocol, participants will be re-tested using the same measures in the pre-test. Expected Results: We expect to see a difference in the sensorimotor integration measures before and after the RSCL exposure period. More specifically, we expect to see results similar to what is seen following concussion. The RSCL exposure data will help to develop a portable sensorimotor integration system for real-time impairment assessment after RSCL incidents in field settings. This system could help prevent neurological injury in sports, military, and other environments while also aiding in the evaluation of conditions like Parkinson’s disease and stroke.
Keywords: Soccer Heading, RSCL